A Precipitation Phenomenon of Titanium Compounds in Aluminum Melts and the Refinement Fading Mechanism of the Al-5Ti-0.62C Master Alloy - Wanwu Ding; Wenjun Zhao; Tiandong Xia (Advances in Materials Science and Engineering)
The Al-5Ti-0.62C master alloy was prepared through a method of thermal explosion in molten aluminum. The process of remelting and refining of commercially pure aluminum was conducted, and precipitation samples with different heat-treatment times were obtained. Scanning electron microscopy (SEM), X-ray diffraction (XRD), optical microscopy (OM), and other techniques were used to analyze the microstructure of the precipitates at the bottom of the samples so as to explore the fading mechanism of Al-Ti-C alloy refinement. The results showed that an obvious precipitation phenomenon of titanium compounds existed in the remelted Al-5Ti-0.62C master alloy and that there were both TiC compounds and TiAl3 compounds in the precipitates; in the refined pure aluminum samples, the precipitates were mainly TiC compounds. Precipitation of titanium compounds in aluminum melting is the main cause of fading in the refinement effect of an Al-Ti-C master alloy.